Менеджмент банківського страхування в умовах євроінтеграції ринку страхових послуг в Україні - Мельник, Т. А.; Коцюрба, О. Ю.; Михайленко, А. Г.; Melnyk, T.; Kotsiurba, O.; Mykhailenko, A. (ЛУБП, 2023)
В статті систематизовані п’ять основних підходів щодо визначення банківського страхування. Пропонується розглядати банківське страхування як комплексну угоду про співпрацю між банком і страховиком щодо визначених аспектів діяльності. Проведена оцінка сучасного стану банківського страхування в Україні. Виявлена тенденція активного продажу банками догорів на ринку страхування життя як страхових посередників. Окресленні основні проблеми розвитку банківського страхування в Україні: виникнення конфлікту інтересів між банком і страховиком, специфічність і складність страхової послуги, невідповідність українського законодавства європейському, недостатній рівень цифрової трансформації ринку фінансових послуг. Запропоновані шляхи вирішення окреслених проблем дозволить розвивати банківське страхування на ринку страхових послуг в Україні, що наддасть додаткової стабільності як банківському так і страховому сектору економіки та сприятиме їх європейській інтеграції. Further development of banking insurance services has become one of the main trends in the financial services market and contributes to the processes related to the European integration of the Ukrainian financial sector. That is why the issue of the bank insurance development in modern unstable conditions remains relevant. The study purpose is to identify the main problems of its European integration and substantiate practical recommendations on management directions for their solution based on the analysis of the state of bank insurance development. Five approaches to determine the bank insurance economic category are systematized and allocated. It is proposed to consider bank insurance as a comprehensive cooperation agreement between the bank and the insurer regarding: - insurance services provision by the bank through insurance agents or insurance brokers; - insurance by the insurer of the bank’s various risks and its staff; - banking services provision by the insurer; - regulation of the ownership structure between the bank and the insurer in the integrated financial group; - innovative universal financial service creation. The assessment of the bank insurance current state in Ukraine showed that cooperation is being formed between banks and insurers to introduce it in the form of concluding insurance contracts through banking institutions. At the same time, Ukrainian banks actively sell up on life insurance as insurance intermediaries, which meets the needs of all participants in the cooperation. The main problems of the bank insurance development in Ukraine are outlined: the emergence of interest conflict between the bank and the insurer, the specificity and complexity of the insurance service, the inconsistency of Ukrainian legislation with European, the insufficient level of the financial services market’s digital transformation. The proposed ways to solve the outlined problems will allow to develop banking insurance in the financial services market in Ukraine, which will give additional stability to both the banking and insurance sectors of the economy.
Bank insurance management in the conditions of the insurance market’s European integration in Ukraine
Keywords: страхування; страховий ринок; страховий менеджмент; співпраця банку і страховика; страховий агент; insurance; insurance market; insurance management; cooperation between the bank and the insurance company; insurance agent